Letter to the Editor Regarding “The Vigil of Medicine” - Schukow, Casey P. (International Journal of Medical Students, 2021)
This letter to the editor is regarding “The Vigil of Medicine”, which is a reflection on the author’s personal experiences backpacking the John Muir Trail. In this piece, the author discusses not being afraid to look back, while seeing the campers behind her holding up a “string of headlights that snake up the mountain”. I agree with the author that this “string of headlights” resembles the journey of medical school. Every year, more students begin their journey into medicine, and as more senior medical students, we have a responsibility of leading our younger classmates behind us. In this letter, I draw on this importance of leadership integrated into medical school curricula (e.g., through student-led organizations) and discuss my time as a Peer Mentor (PM) while as a second-year medical student. As a PM, I was able to provide much support to my first-year classmates through ways such as bringing snacks each weekend, taking walks to a local ice cream store, and running tutoring sessions. When my time as a PM was over, many of my then first-year classmates graduated to become second-years, and gladly took over the program with gratitude as they embarked on leading their incoming freshmen classmates. This opportunity uniquely embodies the concept of the “string of headlights”, and this letter encourages senior medical students to continue leading their younger classmates so the path of headlights can continue to burn bright.